Peranan Syekh Abdoes Shamad Al-Palembani Sebagai Ulama Bebas dalam Proses Internalisasi Islam di Palembang - Amalia, Tita; Hudaidah, Hudaidah (Universitas Hamzanwadi, 2022)
Palembang Darussalam is a Sultanate whose center is located in South Sumatra, precisely in the city of Palembang. A sultan led the Sultanate of Palembang Darussalam. In addition to a sultan, other important figures who also influenced the development of that period were ulama or religious leaders. One of the scholars who was quite popular during the Palembang Darussalam Sultanate was Sheikh Abdoes Shamad Al-Palembani. The purpose of this study is to describe the role of Sheikh Abdoes Shamad Al-Palimbangi as a Free ulama in the Process of Internalization of Islam in Palembang. Through historical research conducted studies with primary sources, manuscripts, secondary sources, and interviews with Islamic figures of Palembang. Then there is the criticism of sources, Auffassung, and historiography. So the role of Sheikh Abdoes Shamad Al-Palimbangi in the internalization of Islam is known to be a teacher of tawhid, fiqh, and neo-Sufism, especially the Tarikat Samaniah, as well as an essential role in teaching Islam in Palembang through his students. Concrete evidence of his role is the manuscripts of his work used to teach and develop Islam in the Sultanate of Palembang Darussalam. Even Zikir Ratib Saman has become a routine activity carried out in mosques until now.Palembang Darussalam adalah sebuah Kesultanan yang pusatnya terletak di Sumatera Selatan, tepatnya di kota Palembang. Seorang sultan memimpin Kesultanan Palembang Darussalam. Selain sultan, tokoh penting lainnya yang turut mempengaruhi perkembangan zaman itu adalah ulama atau tokoh agama. Salah satu ulama yang cukup populer pada masa Kesultanan Palembang Darussalam adalah Syekh Abdoes Shamad Al-Palembani. Tujuan penelitian ini adalah untuk mendeskripsikan peran Syekh Abdoes Shamad Al-Palimbangi sebagai Ulama Merdeka dalam proses internalisasi Islam di Palembang. Melalui penelitian sejarah dilakukan kajian dengan sumber primer, naskah, sumber sekunder, dan wawancara dengan tokoh Islam Palembang. Lalu ada kritik sumber, Auffassung, dan historiografi. Maka peran Syekh Abdoes Shamad Al-Palimbangi dalam internalisasi Islam dikenal sebagai guru tauhid, fiqh, dan neo-sufisme, khususnya Tarikat Samaniah, serta peran penting dalam pengajaran Islam di Palembang melalui murid-muridnya. Bukti nyata perannya adalah naskah-naskah karyanya yang digunakan untuk mengajarkan dan mengembangkan Islam di Kesultanan Palembang Darussalam. Bahkan Zikir Ratib Saman sudah menjadi kegiatan rutin yang dilakukan di masjid-masjid hingga sekarang.